Gut microbiome-brain axis and inflammation in temperament, personality and psychopathology. (April 2022) - Sumich, Alexander; Heym, Nadja; Lenzoni, Sabrina; Hunter, Kirsty
Highlights: Microbiome is associated with temperament from birth through childhood. Associations have been observed between adult personality traits and gut microbiome. Further work is needed to delineate the direction of these relationships. Enrichment of microbiota affect mood and some psychopathologies. Further work will determine whether microbiota enrichment affects personality traits. Abstract : Full understanding of temperament, personality and psychopathology must consider biological mechanisms beyond the brain. Over 4000 species of commensurate microbiota inhabit our bodies and influence almost all aspects of human physiological function. Evidence supports bidirectional relationships between the gut microbiome and brain function. For example, gut environment directly influences limbic function via the vagal nerve, modulating affect and stress-responsivity. In turn, states of distress affect the ecology of the gut, physiologically and through behavioural alteration (diet, social interaction). Furthermore, the gut microbiome modulates the release of inflammatory molecules and hormones, indirectly affecting brain structure and function. Thus, development of gut microbiome from gestation, through birth, during childhood, adulthood and into old age is associated with temperament, personality and psychological wellbeing, including sexual differentiation in psychological function during puberty, and vulnerability to developmental, psychiatric and neurological disorders. Moreover, nutrients known to affect gut function and inflammation (e.g. fatty acids) are associated with temperament and personality in clinical and nonclinical groups. These relationships may reflect the influence of psychological traits on the microbiome by determining how an organism explores the environment, seeks reward, its social interaction and food preferences. However, it might also reflect an effect of microbiome status on psychological function. There is a need for further systematic multidisciplinary studies that integrate psychology, neurosciences, immunology and microbiology to determine the direction of these relationships and fully understand the biological basis of temperament, personality and psychopathology.